Emergence of shared leadership in project teams: The role of events - Marion Karppi; Heli Aramo-Immonen; Ursula Hyrkkänen; Markku Jokisaari (Project Leadership and Society (PLAS), 2024)
The interest in project leadership research has expanded towards shared leadership practices, and shared leadership is a noteworthy alternative for traditional project management approaches. Despite the growing interest in shared leadership, the role of events in the emergence of shared leadership remains unclear. The aim of our research was to identify what kind of events trigger or hinder the emergence of shared leadership in project teams. Our qualitative research data from interviews with 31 project team members was collected in five different organizations. Activity theory was chosen as the analytical tool to explore the events affecting the emergence of shared leadership. We found event chains that trigger and hinder the emergence of shared leadership during the different phases of a project life cycle. Our research contributes to project leadership research by shedding light on the role of events in the emergence of shared leadership.
Keywords: 650; Activity theory; Emergence; Event chains; Project life cycle; Shared leadership